THE EFFECT OF BREED AND SEX ON THE BODY CONFORMATION OF BARB, ARABIAN-BARB, AND ARABIAN HORSES IN ALGERIA - Kacem Nacera (Journal of Animal and Plant Sciences, 2024)
The preservation of genetic diversity in Algerian horse breeds is essential for their effective conservation and utilization. However, a current lack of knowledge about their diversity and genetics presents a significant challenge. This study aims to characterize the morphological features of three principal horse breeds in Algeria: Barb, Arabian-Barb, and Purebred Arab. We measured 26 morphological traits, calculated live weight and eight body indices, and evaluated three qualitative parameters: coat color, muzzle shape, and cephalic profile. Average values for these measurements were computed for each breed. We assessed the significance of these averages using multi-factor ANOVA and compared them using the Newman-Keuls homogeneity test with SAS software. The results reveal distinct morphological characteristics for each breed. The Barb breed has a distance between the internal angles of the eyes of 17.27 cm, a neck length of 63.46 cm, a leg length of 38 cm, an average withers height of 154.2 cm, a live weight of 429 kg, a thoracic perimeter of 175.85 cm, and a compactness index of 2.80. The Purebred Arab displays a distance between the internal angles of the eyes of 18.5 cm, a neck length of 59.5 cm, a leg length of 40.01 cm, an average withers height of 150.3 cm, a live weight of 377.64 kg, a thoracic perimeter of 162.8 cm, and a compactness index of 2.44. The Arabian-Barb breed, a result of crossbreeding, is highly heterogeneous and combines desirable traits from both parent breeds. A significant influence of sex was noted on the height at the withers (p<0.05), with males generally taller than females, who present wider chests and larger lower leg circumferences.
Keywords: horses; index; live weight; morphometric traits.